2009
DOI: 10.1111/j.1745-6584.2009.00606.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Water Velocity in the Capillary Fringe: The Point Velocity Probe

Abstract: The point velocity probe (PVP) is a device that can measure groundwater velocity at the centimeter scale, and unlike devices that measure velocity within well screens, the PVP operates while in direct contact with the porous medium. Because of this feature, it was postulated that the PVP could be effective in measuring velocity within the capillary fringe. This hypothesis was tested using a laboratory flow-through cell filled with a medium-fine sand from Canadian Forces Base Borden. The cell was constructed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…The results presented here are consistent with the findings of Berg and Gillham (2010), who measured the horizontal water velocity using a point velocity probe in a laboratory experiment. They showed that the water velocity profile was continuous from below the water table up to 0.44 m above the water table, corresponding to the air‐entry pressure of the sand used.…”
Section: Resultssupporting
confidence: 92%
“…The results presented here are consistent with the findings of Berg and Gillham (2010), who measured the horizontal water velocity using a point velocity probe in a laboratory experiment. They showed that the water velocity profile was continuous from below the water table up to 0.44 m above the water table, corresponding to the air‐entry pressure of the sand used.…”
Section: Resultssupporting
confidence: 92%
“…Several PVP designs, varying in size and construction materials, have been described in the literature for both laboratory and field studies. These have included probes with stainless steel bodies and accessory parts (Labaky et al ; Berg and Gillham ), polyvinyl chloride bodies with plastic accessory parts and a gas diffuser stone ­injection port (Devlin et al ; Devlin et al ). In each case, the cost of probe construction tended to be dominated by personnel time rather than material costs (Devlin et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, point velocity probes (PVPs) have been used to characterize groundwater velocities in aquifers composed of sand or sand and gravel (Labaky et al , ; Berg and Gillham ; Schillig et al ; Devlin et al 2012). The PVP operates by injecting a small volume of tracer—usually saline—on the surface of a cylindrical probe.…”
Section: Introductionmentioning
confidence: 99%